Building Students’ Strong Personality through Character Education in Schools Under The Implementation of The Merdeka Curriculum: A Strategy for Preventing Demoralization - Maulana, Abdul Holik; Nurihsan, Juntika; Irianto, Dede Margo (International Conference on Elementary Education, 2025)
Character education in schools plays a strategic role in shaping resilient and integrity-driven personalities to prevent the growing phenomenon of demoralization among students in the era of disruption and global value transformation. This study aims to provide an in-depth analysis of the importance of integrating character education into the implementation of the Merdeka Curriculum, as well as to identify an effective conceptual model for strengthening students’ moral development. Employing a qualitative literature review method, this research examines a wide range of recent scholarly sources, including books, journals, and research reports relevant to the themes of character education and the Merdeka Curriculum. The synthesis of literature indicates that systematically integrated character education within the Merdeka Curriculum makes a significant contribution to preventing demoralization through the reinforcement of Pancasila Student Profile values. This study proposes the Integrative Model of Character Education within the Merdeka Curriculum (IM-CE2M), which consists of four key components: (1) project- and experience- based contextual learning that cultivates the values of faith, collaboration, and independence; (2) consistent habituation and self-development programs that foster moral discipline and positive habits; (3) synergistic collaboration among schools, families, and communities as the three centers of value-based education; and (4) strengthening teachers’ capacities as moral role models and primary facilitators of character-based learning. The implementation of IM-CE2M demonstrates that character education not only serves as a means of preventing demoralization but also forms the foundation for developing students who are faithful, critical, creative, and ethical embodying the ideals of the Pancasila Student Profile. Thus, integrating character education within the Merdeka Curriculum represents a transformative strategy to cultivate a young Indonesian generation with strong character, global competitiveness, and steadfast commitment to universal moral and humanitarian values.